Liquid-Solid Reaction Method to Synthesize La0.7Sr0.3MnO3 Powder as Cathode for Solid Oxide Fuel Cell - Si, Jingyu; Bao, Weitao (Asian Journal of Chemistry, 2012)
La0.7Sr0.3MnO3 powders were prepared by liquid-solid reaction method using humidified (3 % H2O) hydrogen as fuel and ambient air as oxidant. These powders were evaluated in terms of phase structure, morphology and fuel cell performances. An electrolyte-supported solid oxide fuel cell was prepared in a conventional manner. The results showed that the formation of La0.7Sr0.3MnO3 perovskite phase was acquired at 1100 ºC for 5 h. The particles of the powders were uniform and were about 0.1-0.3 μm. At 750 ºC, the maximum power density of a single cell with La0.7Sr0.3MnO3 powder were 135 mW cm-2.